The Effect of Lactation Diets Supplemented with Krave AP on Sow and Litter Performance - Mikayla S. Spinler; Jordan T. Gebhardt; Joel M. DeRouchey; Mike D. Tokach; Robert D. Goodband; Jason C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2022)
A total of 105 sows (Line 241, DNA) were used across four batch farrowing groups to evaluate the effects of feeding a feed flavor in lactation diets on sow and litter performance. Sow groups 1 and 2 farrowed in an old farrowing house during the summer months and groups 3 and 4 farrowed in a new farrowing house during the winter months. The farrowing house used for groups 1 and 2 was environmentally regulated by fans and drip coolers to adjust ambient temperature. The farrowing house used for groups 3 and 4 was environmentally controlled to maintain a target temperature by cool cells and fans. Sows were blocked by BW within parity on d 110 of gestation and allotted to 1 of 2 dietary treatments. Dietary treatments were a standard corn-soybean-based lactation diet (control) or the control diet with the addition of 0.05% feed flavor (Krave AP, Adisseo, Alpharetta, GA). Sows were fed their treatment diet from entry to the farrowing house (d 110 of gestation) until weaning at around 19 days of age. Farrowing house environment had a large impact and resulted in many interactions with the lactation feed flavor treatment. Sows fed the flavor treatment had a tendency (P =0.093) for a higher ADFI overall compared with control fed sows. Adding the feed flavor to the diet increased feed intake and piglet ADG in an environment that was warmer where feed intake was suppressed, but had no effect in the new farrowing house where feed intake of all sows was much greater.
Keywords: feed flavor; feed intake; litter performance; sow